A two steps method for electrochemical impedance modeling using fractional order system in time and frequency domains. (May 2019) - Nasser-Eddine, Achraf; Huard, Benoît; Gabano, Jean-Denis; Poinot, Thierry
Abstract: Accurate estimation of electrochemical impedance parameters is related to an appropriate model and the identification method. Electrochemical Impedance Spectroscopy (EIS) allows accurate identification meanwhile it requires a long time to be performed. Chronopotentiometry represents an alternative for EIS especially for low frequencies impedance identification that can be performed faster than EIS. This paper presents a method that combines the EIS and chronopotentiometry in order to identify the impedance parameters of an electrochemical cell. An Equivalent Electric Circuit (EEC) based on Randles circuit is used to describe the impedance aspect of the electrochemical cell. This impedance is represented through fractional systems and is identified using Levenberg–Marquardt algorithm. The validation process is performed using an experimental test bench made of two platinum electrodes immersed into Ferri/Ferrocyanide solution. Results indicate high accuracy for the estimation of the impedance parameters. Highlights: Estimation of diffusion battery parameters in time domain as an alternative to spectroscopic identification methods. Identification of impedance parameters using fractional modeling. Two step method that ensures accurate and fast identification using both frequency and time domains.